2006
DOI: 10.2105/ajph.2005.071035
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Report of Physician-Provided Smoking Cessation Advice: Analysis of the 2000 National Health Interview Survey

Abstract: Some 16 million smokers in the United States could not recall receiving advice to quit smoking from their physician in the preceding year. These missed opportunities, compounded by racial/ethnic disparities such as those observed between Hispanics and other groups and between Hispanic subgroups, suggest that considerably greater effort is needed to diminish the toll stemming from smoking and smoking-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 29 publications
8
77
1
Order By: Relevance
“…Black outpatients less frequently receive advice to quit, and subsequently receive medications less often than white patients. 31,32 A prior study of patients admitted for myocardial infarction indicated that black patients are less likely to be advised to quit smoking, 7 suggesting that this disparity in treatment exists in other inpatient settings. Although the number of black subjects in our study was low, the difference in the odds of treatment is striking.…”
Section: Discussionmentioning
confidence: 99%
“…Black outpatients less frequently receive advice to quit, and subsequently receive medications less often than white patients. 31,32 A prior study of patients admitted for myocardial infarction indicated that black patients are less likely to be advised to quit smoking, 7 suggesting that this disparity in treatment exists in other inpatient settings. Although the number of black subjects in our study was low, the difference in the odds of treatment is striking.…”
Section: Discussionmentioning
confidence: 99%
“…5 We found that light and intermittent smokers were less likely to receive advice from health professionals to quit smoking. Latinos have also been found to receive less advice to quit smoking, 13,14,33 which may be attributable to differences in smoking level after health status is taken into account. 33 Because of the deleterious health effects of smoking and because the odds of successfully quitting are higher when advised by a health professional, 34 it is important that all smokers be advised to quit regardless of smoking level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, prior research has noted lower rates of utilization of pharmaceutical aids in smoking cessation among Latino smokers as well as lower likelihoods of receiving physician advice on quitting. 35,36 A small sample of Latino adults in a qualitative inquiry 37 remarked that one of the top reasons for quitting smoking was concern for family and social standing (e.g., setting a good example), and female participants in particular felt that smoking was an "ugly" behavior. In this study, no participants relied on pharmaceutical aids and female smokers turned to traditional remedies and alternative activities-as opposed to physician advice or medical interventionwhen attempting to quit.…”
Section: Discussionmentioning
confidence: 99%